A re-assessment of Konarus Bamber, 2006 and sympatric leptocheliids from Australasia, and of Pseudoleptochelia Lang, 1973 (Crustacea: Peracarida: Tanaidacea) - Bamber, Roger N (Zootaxa, 2013)
Following recent revelations regarding males with subchelate chelipeds in the tanaidacean genus Parakonarus, a number of Australian leptocheliid taxa are re-assessed, and their males and females variously re-allocated. To assist the interpretation of taxa with subchelate males, Heterotanais anomalus Sars is redescribed based on material from the Balearic Islands. The males of Konarus are now known to have a subchelate cheliped. The male (only) of Pseudoleptochelia bulbus from Melanesia is re-assigned to Konarus cheiris, while Pseudoleptochelia bulbus sensu stricto is reassigned to Leptochelia together with its “minuta”-type male, as Leptochelia bulbus. Pseudoleptochelia straddi is re-assigned to Konarus, together with its females from Queensland, Australia, which were previously assigned to Konarus cheiris. Pseudoleptochelia fairgo is confirmed as a member of Parakonarus, but material from Queensland is re-described as a new species. Other species previously assigned to Pseudoleptochelia are re-assessed: P. inermis, P. mercantilis and P. mortenseni sensu stricto are transferred to Leptochelia. The “small females” and males of P. mortenseni are transferred to Parakonarus as a new species. P. antarctica is provisionally reverted to Heterotanais, P. mergellinae to Leptochelia, and P. filum is tentatively transferred to Pseudonototanais. Pseudoleptochelia magna is synonymized with P. anomala. Pseudoleptochelia provincialis is tentatively transferred to Parakonarus. Pseudoleptochelia occiporta (females only) is reassigned to Leptochelia; the male of P. occiporta is considered to represent a species of Parakonarus. Pseudoleptochelia juliae is reassigned to Parakonarus. Konarus, Makraleptochelia, Bassoleptochelia, Parakonarus and Pseudoleptochelia are placed in the new subfamily Konariinae. Generic relationships in this subfamily were confirmed by Principle Components Analysis. Catenarius is placed in the new subfamily Catenariinae.